Inflammatory Markers in Lung Cancer- A Comparative Cross-sectional Study - Manisha Jain; Mohammed Javed Qureshi; Narendra Khippal; Chand Bhandari; VM Jaanakhi; Karthika Prasad (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Lung cancer is the most common cause of cancer mortality worldwide, principally because of its late diagnosis. Chronic inflammation plays a significant role in tumour growth and progression via increasing the levels of inflammatory markers in blood. Inflammatory markers are expected to be valuable prognostic biomarkers in cancer. Markers like Absolute Neutrophil Count (ANC), Absolute Lymphocyte Count (ALC), platelet count, Neutrophil Lymphocyte Ratio (NLR) and Platelet Lymphocyte Ratio (PLR) may aid in assessing prognosis of lung cancer. Aim: To study the inflammatory markers (ANC, ALC, Platelet count, NLR and PLR) in lung cancer and correlate these markers with cancer stage and histopathological type. Materials and Methods: A hospital-based cross-sectional study was conducted in lung cancer patients at Institute of Respiratory Diseases, SMS Medical College, Jaipur, Rajasthan, India. Sixty patients with lung cancer and sixty controls were included. The clinical characteristics, ANC, ALC, platelet count, NLR and PLR of cases and controls were assessed and compared. Also, the comparison of these inflammatory markers with Tumor, Nodes and Metastases (TNM) staging and histopathological type of lung cancer were documented and results were interpreted. The data analysis was done with the use of Statistical Package for Social Sciences (SPSS) software, IBM manufacturer, Chicago, USA, (Ver.) 26. Results: Mean age (years) of the case and control groups was 60.17 and 61.03, respectively. Distribution of gender in cases and controls was comparable. The major histology of lung cancer was Non-Small Cell Lung Cancer (NSCLC, 81.66%) out of which squamous cell carcinoma constituted 55.00% and adenocarcinoma 21.67%, followed by small cell carcinoma at 18.33%. Overall, 46.67% of the patients belonged to TNM staging IVA followed by IIIB (25.00%). The levels of ANC, platelet count, NLR and PLR were significantly elevated and ALC was decreased in cases as compared to control. There was no statistically significant association between the inflammatory markers ANC, ALC, platelet counts, NLR and PLR with the histopathological type of lung cancer. Mean ANC, platelet count, NLR and PLR were found to be significantly elevated in late stages of lung cancer, whereas, ALC had no such association with the stages of lung cancer. Conclusion: Inflammatory markers (ANC, platelet count, NLR, PLR, ALC) can serve as valuable prognostic biomarkers in lung cancer and can easily be used in resource-limited areas.